Research of fullerene grafting cellulose for functionalized hollow fiber membrane. Issue 180 (4th May 2017) - Zhang, Xin-Feng; Yang, Shu-Jing; Yao, Hong-Wei; Chen, Xu-Feng; Zheng, Xiao-Jun; Li, Ze-Jing; Cong, Hai-Lin
ABSTRACT: Fullerene (C60 ) was successfully grafted on cellulose following with the modification of cellulose by acid chlorination and subsequently azidation. The structures of modified cellulose made by sulfonation, acylating chlorination, Azidation, ionization and fullerenated were determined by infrared spectroscopy. The results show that the raw cellulose can obtain good dissolution property when the methyl imidazole-chloropropylene ionic liquid is used as the solvent system. The choice of intermediates has an important effect on the modification. The better grafting efficiency can be obtained with acyl chlorinated cellulose, and the reactivity and reactivity control of the azided chlorinated cellulose fibers are more easily to obtain. The azided chlorinated cellulose can be grafted by fullerene successfully.